Influence of exercise on functional capacity and in the lumbar and thoracic disability in ankylosing spondylitis - Lopes, Sofia (2015)
Ankylosing Spondylitis (AS) is a chronic inflammatory disease, associated to spine moblity limitations. Until today it isn’t known an efficient treatment; although, there are therapeutic strategies, like exercise, that can alleviate and delay the disease complications.